2013
DOI: 10.1371/journal.pone.0083508
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogens Rescue Neuronal Cell Death through an Activation of AKT and ERK Survival Signaling

Abstract: Neuronal cells are susceptible to many stresses, which will cause the apoptosis and neurodegenerative diseases. The precise molecular mechanism behind the neuronal protection against these apoptotic stimuli is necessary for drug discovery. In the present study, we have found that plasmalogens (Pls), which are glycerophospholipids containing vinyl ether linkage at sn-1 position, can protect the neuronal cell death upon serum deprivation. Interestingly, caspse-9, but not caspase-8 and caspase-12, was cleaved upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 44 publications
4
79
1
Order By: Relevance
“…In the case of our healthy rats, at the age of 1 year, the plasmalogen level in the tissues tended to increase, whereas Norton et al showed no major impact of age [55]. Thus, it seems the plasmalogen status does not indicate any defective function in our rat model, while plasmalogens are crucial, for instance, for Schwann cell development and differentiation [59] or as neuroprotective against apoptosis [60], although the role of the alkenyl species remains poorly documented and requires detailed study. Yamazaki showed a structural evolution in plasmenylcholine and plasmenylethanolamine in metabolic syndrome [61].…”
Section: Discussionmentioning
confidence: 46%
“…In the case of our healthy rats, at the age of 1 year, the plasmalogen level in the tissues tended to increase, whereas Norton et al showed no major impact of age [55]. Thus, it seems the plasmalogen status does not indicate any defective function in our rat model, while plasmalogens are crucial, for instance, for Schwann cell development and differentiation [59] or as neuroprotective against apoptosis [60], although the role of the alkenyl species remains poorly documented and requires detailed study. Yamazaki showed a structural evolution in plasmenylcholine and plasmenylethanolamine in metabolic syndrome [61].…”
Section: Discussionmentioning
confidence: 46%
“…49 Inhibition of cleaved caspase-9 and caspase-3 was also found after the treatment with BMSC-derived exosomes. Serum starvation can induce the processing of full-length caspase-8, 50,51 caspase-9, [52][53][54] and caspase-3, 52 and exosomes inhibit the cleavage of caspase-9 to protect these cells from apoptosis. Furthermore, the prosurvival effect of BMSC-derived exosomes was confirmed with exosomes of both ND and MM patients.…”
Section: Bmsc Exosomes Induce MM Growth and Drug Resistance 563mentioning
confidence: 99%
“…In contrast, there is also accumulating evidence showing that the ERK1/2 pathway is required for neuroprotection (Sanchez et al, 2012). Hossain et al (2013) reported that plasmalogens rescued nutrient deprivation-induced cell death by reducing apoptotic action via activation of Akt and ERK1/2 pathways. In addition, Pignataro et al (2013) demonstrated that ERK1/2 phosphorylation was involved in the neuroprotection produced by remote ischemic post-conditioning.…”
Section: Introductionmentioning
confidence: 99%